PENGARUH MOTIVASI KERJA, PELATIHAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BANK SYARIAH INDONESIA (STUDI KASUS PADA PT. BANK SYARIAH INDONESIA CABANG BLOK M) - Zulfahmi Zulfahmi; Zulfison Zulfison (Journal of Accounting, Management and Islamic Economics, 2023)
Work motivation, job training and organizational culture have a strong relationship with employee performance. This study aims to determine the effect of employee performance, job training and organizational culture on employee performance at PT. Bank Syariah Indonesia Blok M Branch. Population data at Bank Syariah Indonesia Blok M branch is used to measure employe performance. This technique is used if the population has members/elements that are not homogeneous and proportionally stratified (Suharsimi Arikunto, 2005: 98). Empirical results prove that employee performance, job training and organizational culture have a positive effect on improving employee performance. The results of this study are certainly useful for employees of Bank Syariah Indonesia. Furthermore, the role of organizational culture must be increased again because it is proven that organizational culture has an effect on employee performance. By looking at the fact that the influence of Work Motivation, Job Training and Organizational Culture is quite strong, then these factors must be made a special part in terms of implementing work programs to further improve performance.